2016
DOI: 10.1210/jc.2016-1896
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss and Lowering Androgens Predict Improvements in Health-Related Quality of Life in Women With PCOS

Abstract: Both weight loss and OCP use result in significant improvements in several physical and mental domains related to quality of life, depressive symptoms, and anxiety disorders, and combined therapies offer further benefits in overweight/obese women with PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
106
1
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(126 citation statements)
references
References 40 publications
6
106
1
5
Order By: Relevance
“…Women with PCOS and irregular menstrual cycles with hirsutism, had higher anxiety symptoms but not depressive symptoms than control women (86). Among women with PCOS who lost weight during a 16 week intervention with oral contraceptive pills or a lifestyle modification program, anxiety symptoms decreased significantly (87). Clinicians should be aware when treating ovarian hormone related disorders, such as PCOS, that anxiety or affective symptoms may also occur.…”
Section: Epidemiology Of Anxiety Disorders Across the Female Lifespanmentioning
confidence: 99%
“…Women with PCOS and irregular menstrual cycles with hirsutism, had higher anxiety symptoms but not depressive symptoms than control women (86). Among women with PCOS who lost weight during a 16 week intervention with oral contraceptive pills or a lifestyle modification program, anxiety symptoms decreased significantly (87). Clinicians should be aware when treating ovarian hormone related disorders, such as PCOS, that anxiety or affective symptoms may also occur.…”
Section: Epidemiology Of Anxiety Disorders Across the Female Lifespanmentioning
confidence: 99%
“…According to the recent International Evidencebased Guidelines for the Assessment and Management of PCOS, all women with PCOS should be screened and monitored for QOL status to prevent, identify, and manage their health concerns. While these guidelines recommended that improving the QOL of the patients should consider as an important goal of treatment [11,35,36], the effect of OCs on psychological health and QOL of PCOS has been investigated only in a limited number of previous studies [12][13][14][15]. Available data showed that treatment with OC was associated with a signi cant improvement in the QOL in a 16-week randomized controlled trial (RCT) [13], a 12-month RCT [12], and a 6-month observational trial [14].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have been suggested that the management of PCOS can improve both physical and psycho-emotional aspects of QOL [10,12,13]. To assess the effects of OCs on QOL domains, we used a speci c questionnaire with a multi-dimensional concept, which was developed for examining the impact of PCOS or its treatment on psychosocial-emotional, self-image, fertility, sexual function, hirsutism, and obesity-menstrual disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, given that the present study demonstrated no association between pre-training IMAT levels and changes in insulin resistance, or between pre-training vitamin D levels and changes in IMAT, it does not appear that potential benefits of higher vitamin D in PCOS are attributable to lower muscle fat infiltration. Nevertheless, addressing low vitamin D and physical inactivity in women with PCOS may provide significant improvements in quality of life through reductions in adiposity [36]. This may be relevant to other features of PCOS, given that higher vitamin D levels are associated with greater reproductive success in women with PCOS [37], and that there is evidence that vitamin D reduces cytokine secretion through its effects on the NF-κB pathway in adipocytes [38], which may reduce systemic inflammation observed in PCOS.…”
Section: Discussionmentioning
confidence: 99%